Impact of addition of two ether additives with high speed diesel- Calophyllum Inophyllum biodiesel blends on NOx reduction in CI engine - Jeevanantham, A.K.; Nanthagopal, K.; Ashok, B.; Al-Muhtaseb, Ala'a H.; Thiyagarajan, S.; Geo, Varuvel Edwin; Ong, Hwai Chyuan; Samuel, K. John (Elsevier, 2019)
The objective of this work was to compare the effect of diethyl ether (DEE) and methyl tertiary-butyl ether (MTBE) addition to biodiesel and diesel blends on diesel engine. The ethers concentration have been varied in proportion of 5% and 10% on volume basis with biodiesel by keeping the diesel concentration as 50% for all ternary blends preparation. Experimental results revealed that D50-B45-DEE5 ternary blend has shown 5.3% increase in thermal efficiency compared to other ternary blends. On the other hand, D50-B45-MTBE5 and D50-B45-DEE ternary blends have reduced CO emission by 8.1% and 14.8% respectively when compared to high speed diesel fuel. Furthermore, the D50-B40-DEE10 blend and D50-B40-MTBE10 reduce the NOx emission by 32% and 8.8% when compared to HSD at maximum load condition. Significant reduction is noted in HC emission for all ether added ternary blends than that of HSD and biodiesel fuels. However, the smoke emission is decreased marginally for D50-B45-DEE5 than that of HSD fuel. Finally, it is evident that both the DEE and MTBE could be used as viable additive with diesel or biodiesel in binary and ternary forms for diesel engine applications. © 2019 Elsevier Ltd